Multiculturalizm as contemporary sociocultural phenomenon - Танчер, В. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
The article offers an analysis of the trends in the development of world culture, as well as multiculturalism as a phenomenon that has social, political, philosophical aspects. Cultural globalization has as its consequence a number of problems that require sociological consideration using the concepts «national identity», «worldview contradictions», «ethnocultural enclaves», «assimilation», «multiculturalism», «cultural diversity», «cosmopolitanism» and others. This allows us to see the complexity of the solution of these problems, the fruitfulness of using sociological analysis.